THE IMPORTANCE OF INDEPENDENT LEARNING - Suyunova Gulhayo Alisherovna; Shamuradova Naima Muxtarovna (PEDAGOGS, 2024)
Abstract: Independent learning has been a common style of learning process in today’s fast-paced world. It enables learners to take charge of their education, adapt to changes, and achieve continuous personal and professional growth. This article highlights the importance of independent learning, its benefits—such as adaptability, lifelong learning, and confidence—and provides strategies for success. Despite challenges such as isolation and lack of resources, independent learning remains a key tool for navigating modern life and achieving goals.